A Modifikasi Alur Pembelajaran Harian Pada Program Pendidikan Inklusif - RIzka Harfiani; Hasrian Rudi Setiawan (Universitas Muhammadiyah Bangka Belitung, 2019)
Inclusive education is now the focus of attention in efforts to provide educational services for all children, including children with special needs. Various problems are often encountered in the learning process in inclusive classes, for this research aims to analyze the modification of the daily learning flow of inclusive education in Raudhatul Athfal An-Nahl, Jakarta. This study uses a qualitative approach to the type of case study research. Data collection techniques used were observation, interviews, and documentation. Technical analysis of data using the Miles and Huberman interactive analysis model, as well as testing the validity of the data with the triangulation method. The results found a modification of the daily learning flow in RA. An-Nahl consists of pre-opener, opener, energizer, activity, linking and summeryzing, review, mission, and closer. Things to consider in the learning process are engagement, attention span, readiness, activity, reviewing, learning outcomes and parallel learning outcomes. The conclusion of this study shows that the modification of the daily learning flow is able to accommodate the strengths and weaknesses according to the character of each student, and is able to overcome problems in the learning process in inclusive classes